Integrating Local Ecological Knowledge into Elementary Science Learning for Sustainable Development: Enhancing Frog Metamorphosis Understanding and Environmental Literacy in Urban Areas - Dina Selviana; Wati Sukmawati (Postgraduate, University of Mataram, 2026)
This study aims to analyze the influence of the integration of Local Ecological Knowledge (LEK) in science learning on the understanding of the concept of frog metamorphosis and environmental literacy of elementary school students in urban areas. This study uses a quantitative approach with a pre-experimental design of a one-group pretest-posttest involving 30 elementary school students. Data were collected through concept comprehension tests and environmental literacy questionnaires, then analyzed using the N-Gain and ANCOVA tests. The results showed that the average score of concept understanding increased from 56.20 in the pretest to 82.10 in the posttest (N-Gain = 0.59), while the environmental literacy score increased from 60.35 to 85.40 (N-Gain = 0.63). The results of the ANCOVA test showed that the integration of LEK had a significant effect on concept understanding (F = 18.42; p < 0.001; η² = 0.39) and environmental literacy (F = 21.17; p < 0.001; η² = 0.42). These findings show that LEK-based learning is able to improve conceptual understanding and environmental literacy through the association of science materials with the local environmental context. Thus, the integration of LEK is an effective approach to support contextual and sustainable science learning in primary schools.